Quantitative Fourth Moment Theorem of Functions on the Markov Triple and Orthogonal Polynomials. (18th October 2021) - Kim, Yoon Tae; Park, Hyun Suk
Abstract : In this paper, we consider a quantitative fourth moment theorem for functions (random variables) defined on the Markov triple E, μ, Γ, where μ is a probability measure and Γ is the carré du champ operator. A new technique is developed to derive the fourth moment bound in a normal approximation on the random variable of a general Markov diffusion generator, not necessarily belonging to a fixed eigenspace, while previous works deal with only random variables to belong to a fixed eigenspace. As this technique will be applied to the works studied by Bourguin et al. (2019), we obtain the new result in the case where the chaos grade of an eigenfunction of Markov diffusion generator is greater than two. Also, we introduce the chaos grade of a new notion, called the lower chaos grade, to find a better estimate than the previous one.